The Role of Religious Courts in Settling Sharia Economic Disputes in Indonesia: Genealogy Analysis of Constitutional Court Decision Number 93/PUU-X/2012 - Susylawati, Eka; Susanti, Dyah Ochtorina; Hamzah, Moh.; Madani, Nadea Nur Shofia (Journal of Indonesian Legal Studies, 2025)
For more than five decades (Since the implementation of Law Number 3 of 2006, which expanded the jurisdiction of religious courts to resolve Sharia economic disputes, there have been various debates regarding the effectiveness and implementation of this policy. Constitutional Court Decision Number 93/PUU-X/2012 clarified the legal position of religious courts, affirming their exclusive authority to adjudicate Sharia economic disputes. Therefore, this research provides an examination of the evolution of Religious Courts and their authority in resolving Sharia economic disputes following Constitutional Court Decision Number 93/PUU-X/2012, and the implications of implementing this decision. This study is normative research using historical, statutory, and conceptual approaches. The findings of this study indicate that the constitutional evolution of Religious Courts in resolving Sharia economic disputes in Indonesia has made significant progress. Their jurisdiction has been expanded by laws such as Number 3 of 2006 and Number 50 of 2009, which grant authority in Sharia economics and Sharia banking disputes. Constitutional Court Decision Number 93/PUU-X/2012 eliminated the legal dualism of the controversial provisions in Law Number 21 of 2008, ensuring legal clarity and consistency in upholding justice in Sharia economic cases. Following Constitutional Court Decision Number 93/PUU-X/2012, Religious Courts in Indonesia possess absolute authority in resolving Sharia economic disputes. The resolution of Sharia economic disputes by Religious Courts is expected to provide justice and welfare for the parties involved in the disputes.